SEMANTICS OF INSULT IN THE CONTEXT OF THE VERB PARADIGM - K. Novikova (Теория и практика судебной экспертизы)
The paper argues for the possibility of identifying pejorative meaning in statements that contain derogatory verbs when conducting forensic linguistic examination of materials in investigations of alleged insult. The author identifies a group of verbs (on the basis of common semantic, morphological, and derivational properties) expressing generalized value judgment of a person.